Penerapan model Pembelajaran Discovery Learning dan Permainan Smart Case untuk Meningkatkan Hasil Belajar Siswa Kelas VII C SMP Kristen 2 Salatiga - Pangaribowo, Dimas Risqi; Keliat, Natalia Rosa; Sastrodihardjo, Santoso; Hutangoal, Daud Ronald (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
This study is a type of an action class study. The purpose of this researches are used to apply the discovery learning model and smart case strategy in order to improve students’ cognitive learning results and to find out the improvement of students’ affective and psychomotor learning results by applying the discovery learning model and smart case strategy. There were 21 students in VII C Class of SMP Kristen 2 Salatiga used as the samples. The instrument of this research is observation sheets, questionnaires and tests. The descriptive analysis was employed in this study. The results of the cognitive learning result in cycle one show that the students’ percentage fulfilling the minimum criteria (KKM) of 75 is 57,14% and in cycle two it improves into 100%. The students’ psychomotor minimum criteria with a good minimum score (≥ 20) in cycle one reaches 90,47% and in cycle two it improves into 100%. The students’ percentage fulfilling the minimum criteria with a good minimum score (≥ 16) in cycle one is 87,71% and in cycle two it improves into 100%. Based on the results of this study, it is proven that the discovery learning model and smart case game could improve the students’ learning results and to train them to be skillful, active, and independent. Moreover, the students’ curiosity about the materials is so high that it will assist them in improving their learning results.